Sexually transmitted infections among adolescent and young adult patients with obsessive–compulsive disorder - Yi- Chun Ho; Shih- Jen Tsai; Mu- Hong Chen (Taiwanese Journal of Psychiatry, 2023)
Objectives: The association between obsessive–compulsive disorder (OCD) and sexually transmitted infections (STIs) and the effects of OCD medication on STI risk remain unknown. In the present study, we intended to study the risks of subsequent STIs after an OCD diagnosis and the effects of related OCD medications on STI risk. Methods: With the Taiwan National Health Insurance Research Database, we enrolled 15,908 adolescent and young adult patients with OCD and 159,080 age- and sex-matched individuals without OCD between 2001 and 2009, and followed them up until the end of 2011 for subsequent STI diagnoses. Results: The total patients with OCD were significantly more to acquire an STI, with a hazard ratio (95% confidence interval) being 3.25 (2.61–4.03), than their counterparts without OCD (p < 0.05). The associations between OCD medications, including antidepressants, mood stabilizers, and second-generation (atypical) antipsychotic drugs, and subsequent STI risk did not reach any significant differences. Conclusion: In this study, we found that OCD is an independent risk factor of acquiring any STI in the adolescent and young adult population. We recommend that clinicians should be more alert in identifying risky sexual behaviors and STI risks in such patients with OCD.